PEMANFAATAN DIAGRAM TULANG IKAN UNTUK MENINGKATAN MUTU PEMBELAJARAN - Nabila Azmi Hsb; Sohiron Sohiron (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the utilization of the Fishbone Diagram as an analytical approach to improving the quality of learning in educational settings. The research employed a literature review method by analyzing various relevant scientific sources, including books, national and international journal articles, and previous research publications related to educational quality management and cause-and-effect analysis. The collected data were analyzed using a descriptive-analytical approach to identify patterns and implications of Fishbone Diagram implementation in learning quality improvement. The results indicate that the Fishbone Diagram is effective as a systematic analytical tool for identifying the root causes of low learning quality. The main factors identified include teacher competence, instructional methods, learning facilities, teaching materials, and school management. Through structured cause-and-effect mapping, educational institutions are able to design more focused, measurable, and sustainable improvement strategies. The novelty of this study lies in its comprehensive synthesis of the Fishbone Diagram application as an analytical instrument that integrates pedagogical and managerial dimensions of education. This study confirms that the Fishbone Diagram is not only relevant as a quality management tool but also as a practical analytical approach to support strategic decision-making for continuous improvement of learning quality.